2017
DOI: 10.1152/ajplung.00074.2017
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette smoke disrupts monolayer integrity by altering epithelial cell-cell adhesion and cortical tension

Abstract: Chronic obstructive pulmonary disease (COPD) is a major cause of morbidity and mortality. Cigarette smoke (CS) drives disease development and progression. The epithelial barrier is damaged by CS with increased monolayer permeability. However, the molecular changes that cause this barrier disruption and the interaction between adhesion proteins and the cytoskeleton are not well defined. We hypothesized that CS alters monolayer integrity by increasing cell contractility and decreasing cell adhesion in epithelia.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
72
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 70 publications
(80 citation statements)
references
References 44 publications
8
72
0
Order By: Relevance
“…The degeneration of cell adhesion affects its interaction with the actin cytoskeleton, which subsequently leads to the initiation of intracellular signalling cascades. Recent studies demonstrated that E-cadherin and β-catenin were reduced in both cell lines and epithelial cells derived from COPD patients exposed to repetitive CS [32][33][34]. In the present study, Western blot showed that after continuous CSE exposure (20 µg/ mL and 50 µg/mL), the expression levels of E-cadherin and (Fig.…”
Section: Cse Promoted Epithelial Interstitial Transformation and Oncosupporting
confidence: 65%
“…The degeneration of cell adhesion affects its interaction with the actin cytoskeleton, which subsequently leads to the initiation of intracellular signalling cascades. Recent studies demonstrated that E-cadherin and β-catenin were reduced in both cell lines and epithelial cells derived from COPD patients exposed to repetitive CS [32][33][34]. In the present study, Western blot showed that after continuous CSE exposure (20 µg/ mL and 50 µg/mL), the expression levels of E-cadherin and (Fig.…”
Section: Cse Promoted Epithelial Interstitial Transformation and Oncosupporting
confidence: 65%
“…ORIGINAL RESEARCH E-cadherin in COPD is not clear, but decreased expression of E-cadherin on the epithelium is associated with a higher risk for development of COPD in the setting of cigarette smoke exposure (33)(34)(35)(36). Analysis of the SPIROMICS cohort showed that higher serum E-cadherin levels were associated with lower percent emphysema (37). It is possible that increased lung inflammation and epithelial injury leads to lower E-cadherin levels specifically in the epithelium, but higher released or soluble levels of E-cadherin.…”
Section: Original Researchmentioning
confidence: 99%
“…Small airway fibrosis and obliteration probably contribute to physiological airway dysfunction and occur earlier than any development of emphysema. One potential mechanism contributing to small airway fibrosis/obliteration involves altered epithelial integrity [ 64 , 65 ]. Triggers such as cigarette smoke and other environmental air pollutants can trigger these changes to cause inflammation implicated in COPD where cytokine expression increases, mucus production increases and permeability increases in airways [ 66 ].…”
Section: Introductionmentioning
confidence: 99%